Residential tower of the Koło castle in the light of the latest archaeological research - Olszacki, Tomasz; Różański, Artur (Archaeologia Historica Polona, 2022)
The Koło castle (Wielkopolskie voivodeship) is the best-preserved royal stronghold in the broadly defined historical province of Wielkopolska (Greater Poland). The castle owes this status not so much to the scale of the structures preserved to this day (i.e., ruins of the bergfried; the west curtain walls, still visible today in full length and considerable height; the greater part of the north curtain wall; and a section of the south one), but rather to the dilapidated condition of other castles founded by Polish monarchs. For a number of years (1977–1983), the Koło castle was subjected to archaeological research led by Łucja Pawlicka-Nowak (Regional Museum in Konin). Among other things, the excavations uncovered the residential tower discussed in this paper. The excavations at the time covered the western half of the building’s interior, both of its outer southern corners, and the north-western area. The research was resumed in 2019, and the authors of this paper faced the challenge of verifying the earlier fieldwork, the extent of which was very wide and not fully documented. The investigations presented here shed completely new light both on the construction history of the Koło castle, and the issues concerning its chronology, which, in the light of current research, would have been as follows: Casimir the Great acquires the village and founds the town of Koło in 1362; the construction of the castle commences and the work on the site of the residential tower quickly progresses following 1365 (or 1367); the monarch dies in autumn 1370, before or shortly after the unfinished castle is consumed by fire. The article concludes with a chapter showing the Koło tower against the background of similar structures in Europe.